THE USEFULNESS OF CORONARY CTA IN IDENTIFYING CASES OF CORONARY ARTERY DISEASE - KALSOOM , F; TARIQ , S; ZAFAR , U; MUSHTAQ , K (Biological and Clinical Sciences Research Journal, 2024)
Ischemic heart disease is the leading cause of mortality worldwide. A complete diagnosis assessment is essential for patients with suspected CAD since it influences many treatment decisions. Invasive coronary angiography is the gold standard for detecting CAD. Objective: To investigate the diagnostic effectiveness of coronary computed tomography angiography (CTA) in diagnosing coronary artery disease. Method: This cross-sectional research comprised 100 patients with suspected coronary artery disease admitted to the Chaudhary Pervez Ellahi Institute of Cardiology Hospital between March 2022 and March 2023. All patients received a coronary CTA and coronary angiography. The findings of the patients' coronary CTAs and coronary angiography were evaluated. The practical uses of coronary CTA in the identification of CAD were investigated, as well as the identification and coincidence frequency of coronary CTA for assessing the degree of coronary stenosis. Results: There were no significant differences between coronary CTAs and coronary angiographies in detecting positive CAD or coronary stenosis. Regarding identifying coronary artery disease, coronary CTA had a sensitivity of 81.69% (58/71) and a specificity of 75.8% (22/29). The positive predictive value was 90.6% (58/64), while the negative predictive value was 62.8% (22/35). The coronary CTA findings revealed that 18 patients had coronary stenosis of no more than 70% and 40 patients had coronary stenosis of more than 70% among the total 58 patients with coronary artery disease that were found using both coronary angiography and coronary CTA. According to the findings of the coronary angiography, there were 37 patients with coronary stenosis greater than 70% and 21 patients with coronary stenosis below seventy percent. P value p=0.326 indicates that no significant differences were detected. Conclusions: In conclusion, coronary CTA has a beneficial and valuable role in the early detection of CAD. It is non-invasive and simple to use. Furthermore, coronary CTA can precisely find the locations of coronary stenosis and determine the degree of stenosis. As a result, it merits widespread adoption as a CAD screening tool.